Nanoparticle Delivery and Tumor Vascular Normalization: The Chicken or The Egg? - Mattheolabakis, George; Mikelis, Constantinos M. (Frontiers in Oncology, 2019)
Tumor-induced angiogenesis has been a significant focus of anti-cancer therapies for several decades. The immature and “leaky” tumor vasculature leads to significant cancer cell intravasation, increasing the metastatic potential, while the disoriented and hypo-perfused tumor vessels hamper the anti-tumor efficacy of immune cells and prevent the efficient diffusion of chemotherapeutic drugs. Therefore, tumor vascular normalization has emerged as a new treatment goal, aiming to provide a mature tumor vasculature, with higher perfusion, decreased cancer cell extravasation, and higher efficacy for anti-cancer therapies. Here we propose an overview of the nanodelivery approaches that target tumor vasculature, aiming to achieve vascular normalization. At the same time, abnormal vascular architecture and leaky tumor vessels have been the cornerstone for nanodelivery approaches through the enhanced permeability and retention (EPR) effect. Vascular normalization presents new opportunities and requirements for efficient nanoparticle delivery against the tumor cells and overall improved anti-cancer therapies.